Development of An Academic Supervision E-Module Based on Coaching to Enhance Teachers' Pedagogical Competence - Shobariyah, Endang; Dwikurnaningsih, Yari (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to develop an interactive and practical academic supervision e-module based on coaching to enhance teachers' pedagogical competence. The research employs a Research and Development (R&D) method using mixed approaches. The study subjects consist of five school principals and five teachers at the Ki Hajar Dewantara Elementary School, the Education Coordinator, Semarang Regency, Central Java Province, following the development procedures of the Borg and Gall model. Product trials were conducted using a Pre-Experimental Design. Data were collected through interviews, questionnaires, and observations. Product validation involved two expert validators (content and IT experts) using both qualitative (data and source triangulation) and quantitative (validity) approaches for data validation. Data analysis was carried out both qualitatively and quantitatively using the Mann-Whitney statistical test. The product validation by experts resulted in an average score of 91.2% (categorized as very valid) for content feasibility and 88.5% (valid) for technological aspects. The validation outcomes revealed an average score of 91.2% (very valid) for content and 88.5% (valid) for technology. The trial results showed an improvement from 19.2% before coaching to 97.2% after coaching, shifting the category from "fair" to "excellent." The Mann-Whitney test results also indicated a significant difference in teachers' pedagogical competence before and after coaching in academic supervision. Additionally, qualitative findings highlighted that the e-module provides easily accessible practical guidance and helps school principals deeply understand coaching techniques. In conclusion, the academic supervision e-module based on coaching is valid and effective in enhancing teachers' pedagogical competence.